Identifying Technology Transfer in Foreign Direct Investment: Influence of Industry Conditions and Investing Firm Motives - Chung, Wilbur (Journal of International Business Studies, 2001)
Firms have different motives for investing abroad, most notably to exercise existing capabilities, but also to build new capabilities by accessing knowledge located abroad. Recognizing this heterogeneity helps determine whether foreign investments transfer technology to their host industries. Using host industries' initial level of competition to differentiate when each of these dichotomous motives is more likely, I examine change in productivity resulting from inward FDI in US manufacturing industries for 1987 through 1991. While controlling for change in industry competition, I find that relatively uncompetitive industries experience productivity growth while competitive industries experience productivity stagnation from FDI. This differential outcome is consistent with heterogeneous investment motives.